Nexus of information asymmetry, environmental externalities and financial performance: Evidence from listed Nigerian campanies - Confidence Joel Ihenyen; Ebipanipre Gabriel Mieseigha (Trends Economics and Management, 2020)
Purpose of the article: There is dearth of empirical studies on the association between information asymmetry, environmental externalities and financial performance, especially in Nigeria. Thus in this paper, we examined the nexus of information asymmetry, environmental externalities and financial performance of listed Nigerian firms. Methodology/methods: In order to attain this, the ex-post facto design was adopted and the simple random sampling technique was used in selecting ten (10) firms in the industrial and consumer goods subsector with data spanning from 2012-2017. The data were obtained from the financial statements of the companiws and the Nigerian Stock Exchange Factbook, while the analysis was carried out via the ordinary least square, fixed and random effects statistical tool. Scientific aim: This paper assessed the nexus of information asymmetry, environmental externalities and financial performance in Nigeria. Findings: The study found a clear indication that the level of financial performance of industrial and consumer goods companies in Nigeria is significantly influenced by the information asymmetry, as well as environmental externalities. Contributions: In view of the findings, it was recommended that there should be collaboration between the government and regulatory framework of accounting in order to advance a robust and clear-cut legislation on disclosure of environmental externalities and information irregularity in the financial statements of companies. Also, this study contributes to knowledge by filling the gap in literature, as well as showing that apart other dynamics that may influence financial performance, information asymmetry and environmental externalities are seemingly fundamental.
Keywords: M40; M41; M49; 650; information asymmetry; environmental externalities; financial performance; Nigeria